More than 100 UMP alumni attended Hi-Tea aimed at fostering closer ties - Nurizzatul Alin, Ahmad Bastani (2019)
A total of 124 Universiti Malaysia Pahang (UMP) alumni turned up for the Alumni Industry Networking Hi-Tea for the western zone organised by Department of Student Affairs and Alumni (JHEPA)’s Alumni Relation Unit, together with Department of Industrial and Community Relation (JJIM).